PENGARUH LITERASI KEUANGAN DAN GAYA HIDUP TERHADAP PERILAKU KEUANGAN GENERASI Z PADA PENGGUNAAN SHOPEE PAYLATER - Al Husaini , Padlan; Sissah, H.; Habibah, G.W.I Awal (Gapenas Publisher, 2025)
The development of digital technology and global economic transformation has led to the emergence of digital financial services such as Shopee PayLater, which is increasingly popular among Generation Z. This generation is known to be adaptable to technology, but on the other hand, they face challenges in terms of financial literacy and consumption control. In the city of Jambi, the use of Shopee PayLater has increased significantly in line with the consumptive lifestyle that has begun to develop among young people. The low level of understanding of financial risks and debt management is a major issue that needs to be further examined. This study aims to analyze the effect of Shopee PayLater usage on the financial behavior of Generation Z in Jambi City, taking into account aspects of financial literacy and lifestyle. The results show that financial literacy has a significant effect on the financial behavior of Gen Z Shopee PayLater users, while lifestyle has no significant effect. However, simultaneously, financial literacy and lifestyle together have a significant influence on financial behavior. This shows the importance of financial literacy in shaping wise financial decisions, as well as the need to strengthen Sharia-based education to encourage healthy and responsible financial behavior